2006
DOI: 10.1634/stemcells.2006-0108
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Mesenchymal Stem Cells in Human Bone Marrow After Exposure to Chemotherapy: Evidence of Resistance to Apoptosis Induction

Abstract: For various potential clinical applications, the use of autologous human MSCs (hMSCs) would be favorable. In vitro observations suggested that hMSCs are resistant for chemotherapeutic substances; however, no data exist on the characteristics of hMSCs from bone marrow (BM) of chemotherapeutically treated patients. Here, we analyzed the character of hMSCs derived from chemotherapy-exposed BM and the in vitro response of hMSCs to chemotherapeutic substances. Colony-forming units-fibroblast (CFU-Fs) were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 43 publications
(49 reference statements)
8
87
4
3
Order By: Relevance
“…In contrast to our study, one focused on the effects of several chemotherapeutic agents used alone in vitro [30]; the other study did however present the effects of chemotherapy on MSCs in vivo but it did not focus on hematopoietic cell support. In addition, while their findings suggest that chemotherapy has no effect on MSC expansion and phenotype, there were several differences between our studies, for example differences in population sizes, experimental methods, times between last chemotherapy administration and bone marrow harvest, and most importantly chemotherapy dose and/or regimens used in the patient cohorts [42].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast to our study, one focused on the effects of several chemotherapeutic agents used alone in vitro [30]; the other study did however present the effects of chemotherapy on MSCs in vivo but it did not focus on hematopoietic cell support. In addition, while their findings suggest that chemotherapy has no effect on MSC expansion and phenotype, there were several differences between our studies, for example differences in population sizes, experimental methods, times between last chemotherapy administration and bone marrow harvest, and most importantly chemotherapy dose and/or regimens used in the patient cohorts [42].…”
Section: Discussionmentioning
confidence: 59%
“…Thus, only the higher proliferating, less-affected MSC-derived stromal cultures were used in the comparative analysis between the high-dose and notreatment patient groups in these experiments. Two previous studies have suggested that MSCs are resistant to chemotherapeutic agents at clinically relevant doses [30,42]. In contrast to our study, one focused on the effects of several chemotherapeutic agents used alone in vitro [30]; the other study did however present the effects of chemotherapy on MSCs in vivo but it did not focus on hematopoietic cell support.…”
Section: Discussionmentioning
confidence: 84%
“…Accordingly to previous reports, bone marrow derived MSCs are resistant to chemotherapeutic agents and irradiation (Chen et al 2006;Li et al 2004;Mueller et al 2006). In contrast, there are no studies in the literature regarding for the chemosensitivity of ADMSCs, this prompted us to analyze the acute and direct reaction of cultured ADMSCs exposed to single chemotherapeutic agent in vitro compared with that of TGCT cell line 2102EP which has been known of high sensitivity.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, BMMSCs are resistant to chemotherapy-induced apoptosis [98][99][100] and contribute to generating drug resistance in tumor cells [95,101]. Likewise, several studies have evidenced that hMSCs are highly resistant to ionizing radiation [102].…”
Section: Mscs and Tumor Growthmentioning
confidence: 99%